Nilai Pasar, Aset Tetap, Profitabilitas, Struktur Modal dan Nilai Perusahaan pada Perusahaan yang Melakukan IPO di Tahun 2013 - Matilda Matilda (Jurnal Manajemen Bisnis dan Kewirausahaan, 2022)
This research aims to find out financial performance of firms that conduct an IPO of shares in the year of 2013 which are listed in the Indonesian Capital Market (Bursa Efek Indonesia) for observation period 2013 until 2016, using Tobin’s Q model. To get the value of Tobin’s Q, data are collected form internet, such as financial statement and closing stock price. Companies with highest Q value (overvalued condition) illustrates that the company has high investment growth. Which variations are influenced by variations of free variables such as market value, tangibility, profitability, and capital structure. The specific uniqueness is emperical data are generally applied for IPO-firms. Because IPO is a phenomenon of the early phase of growth. This research conducted by using Eviews 8. Model 1 uses random effect model. Model 2 uses fixed effect model. The conclusion of this research is that market value, tangibility dan profitability have significant influence for capital structure. Futhermore, firm value would be more fit with capital structure as compared to profitability. Because profitability of firms that conduct an IPO of share is negative.